2019
DOI: 10.1371/journal.pone.0208688
|View full text |Cite
|
Sign up to set email alerts
|

Basic knowledge of social hierarchies and physiological profile of reared sea bass Dicentrarchus labrax (L.)

Abstract: The effects of social hierarchies (dominant/subordinate individuals), such as aggressiveness, feeding order, and territoriality, are some of the characteristics used for describing fish behaviour. Social hierarchy patterns are still poorly understood in European-reared sea bass (Dicentrarchus labrax). In this work, we examine the social interactions among captive fish integrating behavioural and physiological profiles. Groups of three fish with EMG (electromyogram) radio transmitters were monitored for two wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 92 publications
5
24
0
Order By: Relevance
“…Jepsen et al [25] reported similar observations in Chinook salmon, where physiological stress indicators were higher up to 24 h following tag implantation, but were comparable with those of untagged fish at most 7 days later. In our experiments, 46 and 95 days after tag implantation in sea breams and sea bass, respectively, the levels of all monitored stress indicators (cortisol, glucose and lactate) were found to be similar to those of untagged fish and consistent with the levels reported in the literature regarding these species [7,28]. Our results confirm that tag implantation does not induce chronic stress in either the sea bream or the sea bass, as observed in various other fish species [25,29].…”
Section: Discussionsupporting
confidence: 90%
“…Jepsen et al [25] reported similar observations in Chinook salmon, where physiological stress indicators were higher up to 24 h following tag implantation, but were comparable with those of untagged fish at most 7 days later. In our experiments, 46 and 95 days after tag implantation in sea breams and sea bass, respectively, the levels of all monitored stress indicators (cortisol, glucose and lactate) were found to be similar to those of untagged fish and consistent with the levels reported in the literature regarding these species [7,28]. Our results confirm that tag implantation does not induce chronic stress in either the sea bream or the sea bass, as observed in various other fish species [25,29].…”
Section: Discussionsupporting
confidence: 90%
“…Same observations were done in Chinook salmon by Jepsen et al [21], where physiological stress indicators were higher up to 24 h following the tag implantation but were comparable with untagged fish at least 7 days following the tag implantation. In our experiments, after 46 days for bream and 95 days for sea bass following the tag implantation, the levels of all stress indicators monitored (cortisol, glucose and lactate) were found to be similar to untagged fish, and consistent with the literature for these species [7,24]. Our results support the fact that the implantation of a tag does not induce chronic stress in sea bream and sea bass, as already observed for various fish species [21,25].…”
Section: Discussionsupporting
confidence: 91%
“…Jepsen et al [25] reported similar observations in Chinook salmon, where physiological stress indicators were higher up to 24 h following tag implantation but were comparable with those of untagged sh at most seven days later. In our experiments, 46 and 95 days after tag implantation in sea breams and sea bass, respectively, the levels of all monitored stress indicators (cortisol, glucose and lactate) were found to be similar to those of untagged sh and consistent with the levels reported in the literature regarding these species [7,28]. Our results con rm that tag implantation does not induce chronic stress in either the sea bream or the sea bass, as observed in various other sh species [25,29].…”
Section: Discussionsupporting
confidence: 90%